Recycling of sewage sludge ash in cold-bonded artificial lightweight aggregate for sustainable lightweight concrete - Junsong Jiang; Xianliang L. Zhou; Yantao T. Zheng; Ping Wu; Guichuan Jiang; Bingxi Jian (Scientific Reports)
Abstract The cold bonding technology for producing lightweight aggregates has received significant international attention in the fields of waste treatment and the production of green building materials. In this study, sustainable lightweight aggregate concrete (LAC) is prepared by partially replacing natural coarse aggregate with cold-bonded sewage sludge ash lightweight aggregate. The properties and microscopic characteristics of concrete were studied. The results show that the density and compressive strength of LAC decreased to 1645 kg/m3 and 12.83 MPa when the replacement rate of lightweight aggregates from 0 to 100%, indicating that the LAC can be used for non-structural LAC. Structural LAC can also be designed when 75% lightweight aggregates and 25% natural coarse aggregate are used simultaneously. In addition, the results of Scanning Electron Microscope and Nuclear Magnetic Resonance show that high lightweight aggregate content is accompanied by higher porosity and pore size inside the LAC, which reduces the resistance of concrete to drying shrinkage and freeze-thaw cycles. This research provides theoretical support for the application of SSA in sustainable LAC and reducing the damage of SSA to the environment.